Aktivitas Imunomodulator Ekstrak Buah Mengkudu pada Mencit yang Diinfeksi Staphylococcus aureus (IMMUNOMODULATORS ACTIVITY OF NONI (MORINDA CITRIFOLIA L.) FRUIT EXTRACT IN MICE INFECTED WITH STAPHYLOCOCCUS AUREUS) - Mufidah, Zumrotul; Rifa’i, Muhaimin; Rahayu, Sri (Jurnal Veteriner, 2013)
This study aim was to determine the immunomodulatory activity of noni (Morinda citrifolia L.) fruitextract in mice infected with Staphylococcus aureus. Mice were divided into two group :  non-infected  andinfected. Non Infected group was without S. aureus infection whereas the infected group was infected withS. aureus. Group contain control, dose 1 (25 mg/kg BW), dose 2 (100 mg/kg BW), and dose 3 (300 mg/kg BW).Oral treatment carried out for 20 days in every morning and each sample was injected with  S. aureus atday 21 with 109 cell/mL. Relative number of T cell (CD4+, CD4+CD25+),) and cytokine interferon-ã fromCD4+ T cell (CD4+IFN-ã+) subsets was measured using the BD FACSCaliburTM Flowcytometer. Data wereanalyzed by using Analysis of Varians (p<0,05) and SPSS 16 for windows. The result showed thatadministration of noni crude extract was significantly change the relative number of CD4+, CD4+IFN-ã+,and CD4+CD25+ T cells. Treatment of noni crude extract in non-infection group could increase  relativenumber of CD4+, CD4+IFN-ã+  and CD4+CD25+ T cells that might be caused by active compounds of noni asmitogen.  Giving of noni crude extract in infected group could reduce  the relative number of CD4+, CD4+CD25+and CD4+IFN-ã+ T cells due to it  active compounds as anti-inflamation. Noni fruit extract can be used aspreventive therapy on S. aureus infection  because it contains active compounds as an anti-inflammationeffect.
Keywords: Morinda citrifolia, Staphylococcus aureus, immunomodulators